Quo Vadis Indonesian Agrarian Reform: Implementation of UUPA in the President Regulation No. 86 of 2018 - Arsan Nurrokhman Nurrokhman (Pusat Penelitian dan Pengabdian kepada Masyarakat, Sekolah Tinggi Pertanahan Nasional, 2019)
Law Number 5 of 1960 concerning Basic Regulations on Agrarian Principles (UUPA) is widely praisedas the great work of the Indonesian nation which is revolutionary and responsive, combining good elements between individualism and communalism. However, the unachieved objectives of the UUPA is hard to deny and the majority of the defense of its failure tends to be normative and ideological. This paper aims to bring the study of the UUPA to a more empirical direction by using theories of public policy implementation, as introduced byGrindle (1980) about content variables and policy contexts, and the theory of critical implementation researchers who use a bottom-up perspective and highlight the actions of implementing bureaucrats. The research used qualitative methods through the study of literature and focused on executive policy, bureaucrats’ actions and the context that surrounds them. The study found that the executive policy with the issuance of Presidential Regulation of the Republic of Indonesia Number 86 of 2018 was precisely not in line with several provisions of the UUPA. The presidential regulation has a paradox, wants to accommodate many variables but is confused about the main purpose of agrarian reform. As a relatively top-down policy, the implementation of the UUPA requires the existence of a dominant actor. However, the actions of implementing bureaucrats have long reducedthe purpose of the law to merely being an act of legalization of accounting transactions for land that are running according to market mechanisms. Now, the increasing number of Indonesians living in urban areas makes the issue of land more complex, related to land use change and various challenges of sustainable development.